2016
DOI: 10.1016/j.annemergmed.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of EDACS Versus ADAPT Accelerated Diagnostic Pathways for Chest Pain: A Pragmatic Randomized Controlled Trial Embedded Within Practice

Abstract: There was no difference in the proportion of patients discharged early despite more patients being classified as low risk by the EDACS-ADP than the ADAPT-ADP. Both accelerated diagnostic pathways are effective strategies for chest pain assessment and resulted in an increased rate of early discharges compared with previously reported rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
29

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 19 publications
(28 reference statements)
2
92
0
29
Order By: Relevance
“…75 A subsequent validation of the EDACS-ADP using a Canadian cohort of patients classified a similar proportion of patients as low risk with optimal sensitivity and NPV. 76 The EDACS-ADP has been validated in an RCT 77 and is now being used in multiple hospitals in New Zealand and Australia.…”
Section: State Of the Artmentioning
confidence: 99%
“…75 A subsequent validation of the EDACS-ADP using a Canadian cohort of patients classified a similar proportion of patients as low risk with optimal sensitivity and NPV. 76 The EDACS-ADP has been validated in an RCT 77 and is now being used in multiple hospitals in New Zealand and Australia.…”
Section: State Of the Artmentioning
confidence: 99%
“…ADPs required troponin measurement on arrival and then at 1, 2, or 3 hours to determine eligibility for early discharge. ADPs that were considered were the 2-Hour Accelerated Diagnostic Protocol to Assess Patients With Chest Pain Symptoms Using Contemporary Troponins as the Only Biomarker (ADAPT) 10,14 ; Emergency Department Assessment of Chest Pain Score (EDACS) 15,17,18 ; History, ECG, Age, Risk Factors, and Troponin (HEART) 11,19 ; the High Sensitivity Cardiac Troponin T Assay for Rapid Rule-Out of AMI (TRAPID-AMI) 20,21 ; and the new Vancouver Chest Pain Rule. 13 Before implementation, there were meetings involving the first author and representatives from each stakeholder group (including but not limited to the ED, cardiology, general medicine physicians and nurses, hospital management, diagnostic laboratory directors, cardiac technicians, and hospital data analysts).…”
Section: Intervention Phasementioning
confidence: 99%
“…8,[10][11][12][13] Randomized implementation trials of clinical pathways incorporating ADPs at Christchurch Hospital (Christchurch, NZ) demonstrated that early safe discharge rates could be improved (from 11.0% to 32.3%). 14,15 Immediate and successful implementation of clinical pathways incorporating an ADP at Christchurch Hospital prompted the New Zealand Ministry of Health to mandate that all hospitals implement similar clinical pathways for possible ACS.…”
mentioning
confidence: 99%
“…Newer bespoke tools have been developed for assessing risk in ED populations such as the Manchester Acute Coronary Syndromes rule,30 the Christchurch Emergency Department Acute Coronary Syndrome ADP31 and the Triage rule-out using hs-cTnI ADP,32 and future prospective comparison of these scores with HEART will prove important.…”
Section: Discussionmentioning
confidence: 99%